Hubungan Presiden dan DPR - Isra, Saldi (Mahkamah Konstitusi Republik Indonesia, 2013)
Relation between executive and legislative tends to be intricate. Both parties often do not understand the functions and authorities of their respective institutions. At the end, disputes often emerge in playing their roles. This writing tries to discuss the problems concerning two state institutions: the President and the Parliament. The analysis will also address how both institutions manage themselves constitutionally in order not to solely immerse in political interests.